Wave pattern and resistance prediction for ships of full form - Peng, Heather; Ni, Shaoyu; Qiu, Wei (Ocean engineering, 2014)
There are difficulties in predicting resistances for ships of full form based on Dawson׳s method. This paper presents a modified Dawson method to improve the prediction of wave pattern and wave-making resistances for ships of full form. In the proposed approach, an alternative method was first developed so that the free surface boundary conditions are satisfied on arbitrary body-fitted lines instead of streamlines. A stern region was then excluded from the computational domain. Validation studies have been carried out for various ship hulls. There is a good agreement between the computed results and experimental data. It has been demonstrated that the present method improves the numerical stability in evaluating the flow field, wave pattern and wave-making resistance for full-form ships. •A modified Dawson method to improve the prediction of wave pattern and wave-making resistances for ships of full form.•The free surface boundary conditions are satisfied on arbitrary body-fitted lines instead of streamlines.•A stern region was excluded from the computational domain to improve the stability of computation for ships of full form.•Validation studies were carried out for various ships of full form.